Contrasting patterns of energy metabolism in northern vs southern peripheral European flounder populations exposed to temperature rising and hypoxia. (August 2017) - Pédron, Nicolas; Le Du, Jessy; Charrier, Grégory; Zambonino-Infante, José-Luis; Le Bayon, Nicolas; Vasconcelos, Rita P.; Fonseca, Vanessa F.; Le Grand, Fabienne; Laroche, Jean
Abstract: A two months common garden experiment was carried out to explore the potential differences of energy metabolism in northern core (France, 50°N and 47°N) vs southern peripheral (Portugal, 41°N) populations of European flounder Platichthys flesus, submitted to cold condition (CC: water temperature = 10 °C) and to warm and hypoxic condition (WHC: water temperature = 22 °C, and moderate hypoxia with O2 saturation = 40% during the last 6 days). Convergent growth rates (in length) were observed in the different populations and conditions, when the southern peripheral population of Portugal did not grow under cold conditions. A general reduction in liver lipid storage was observed in all populations subjected to WHC when compared to CC, whereas muscle lipid storage was unaffected. The thermal and hypoxia treatment induced changes in muscle phospholipids (PL) ratios: phosphatidylserine/PL, phosphatidylinositol/PL, between northern and southern populations. Fish from northern estuaries displayed marked anaerobiosis in WHC (increased liver LDH activity) vs marked aerobiosis under CC (higher muscle CS and CCO activities). Contrariwise, fish from the southern estuary displayed equilibrium between anaerobiosis and aerobiosis activities in WHC. Flounders from the southern population exhibited generally lower G6PDH activity (proxy for anabolism and for defense against oxidative damage), tissue-specific anaerobiosis response (muscle LDH activity) and lower CS and CCO muscle activities (aerobiosis markers) when compared to northern populations. Globally, these inter-population differences in bioenergetics suggest that southern peripheral vs northern core populations have developed differential capacity to cope with interacting stressors and that much of this variation is more likely due to local adaptation.